1991
DOI: 10.1902/jop.1991.62.10.598
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate and Fibronectin Improve the Capacity of Collagen Barriers to Prevent Apical Migration of the Junctional Epithelium

Abstract: The objective of the present study was to assess the effect of bilayered/collagen barriers enriched with fibronectin and heparan sulfate on the prevention of apical migration of the epithelium during the initial stage of periodontal wound healing. Experimental osseous defects were produced on the labial aspect of maxillary canines in dogs. Experimental sites were treated with either bilayered enriched collagen barriers or with non-enriched bilayered collagen barriers, using the guided tissue regeneration techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…33 In addition to cross-linking, heparan sulfate and fibronectin have also been added in an attempt to enhance the inhibitory effect on epithelial migration. In a dog model, Pitaru et al 37 compared the length of the root surfaces repopulated by connective tissue between sites treated with collagen membrane alone, and those treated with a fibronectin and heparan sulfate-enriched collagen membrane. Approximately 30% more root surfaces were repopulated with connective tissue in the fibronectin and heparan sulfate-treated group compared to the collagen alone group.…”
mentioning
confidence: 99%
“…33 In addition to cross-linking, heparan sulfate and fibronectin have also been added in an attempt to enhance the inhibitory effect on epithelial migration. In a dog model, Pitaru et al 37 compared the length of the root surfaces repopulated by connective tissue between sites treated with collagen membrane alone, and those treated with a fibronectin and heparan sulfate-enriched collagen membrane. Approximately 30% more root surfaces were repopulated with connective tissue in the fibronectin and heparan sulfate-treated group compared to the collagen alone group.…”
mentioning
confidence: 99%
“…Collagen membranes have extensively been investigated in animal models (Pitaru et al 1987(Pitaru et al , 1988(Pitaru et al , 1989(Pitaru et al , 1991Pfeifer et al 1989;Hyder et al 1992;Crigger et al 1996;Tal et al 1996) and human clinical studies (Al Arrayed et al 1995;Zitzmann et al 1997;Hockers et al 1999) presenting good clinical results for periodontal and bone regeneration.…”
mentioning
confidence: 99%
“…In an animal study measuring GTR outcomes, Pitaru et al (1991) concluded that the enrichment of barrier membranes with a combination of fibronectin and heparan sulfate promoted re-population of the surgically exposed root surfaces by connective tissue cells and prevented the apical migration of the epithelium during the first 20 days of healing, relative to sites receiving untreated membranes. A synthetic heparan sulfate mimetic has also been shown to induce healing in experimental craniotomy defects, by enhancing chemotaxis and differentiation of osteoprogenitor cells, and by increasing angiogenesis (Lafont et al, 2004).…”
Section: Biomolecules In Regenerationmentioning
confidence: 99%
“…For delivery, the surgical grafting materials and barrier membrane would either be pre-treated in a solution of perlecan, similar to the application of heparan sulfate and fibronectin to membranes by Pitaru et al (1991), or pre-treated with a vector delivery system, preferably in a sterile buffer such as phosphate buffer, pH 7.4. The pre-treatment may be performed during surgery, or at any time prior to the surgery, provided that the coated surgical implant material is not subject to denaturing temperatures at any time after pre-treatment, and would involve immersion in the perlecan solution for a short period of time.…”
Section: Applicationmentioning
confidence: 99%